Hubungan Tugas Keluarga tentang Kesehatan Terhadap Kualitas Lansia dengan Hipertensi di Posbindu Kelurahan Jatikramat Kecamatan Jatiasih Kota Bekasi - Meiliningtyas, Crysuci; Isnaeni, Isnaeni (Universitas Malahayati, 2024)
ABSTRACT The elderly are part of the growth and development process. The role of the family has a position as the main support. Family duties regarding health are one of the factors to improve the quality of life of elderly people with hypertension so that the elderly can comply with treatment to become stable and prevent further disease complications. to determine the relationship between the implementation of family health tasks regarding hypertension on the quality of life of the elderly and hypertension in Posbindu Elderly, Jatikramat Village, Jatiasih District, Bekasi City in 2023. This research uses descriptive analysis which studies and analyzes the description of